The role of apologies in resolving medical disputes - Jahn Kassim, Puteri Nemie; Saleh, Muhammad Ridhwan (Universiti Putra Malaysia, 2017)
In the wake of medical errors and potential lawsuits, apologies made by medical practitioners to their patients have the ability to defuse prospects of litigation. Often, when things go wrong, patients want to know what actually happened, why it happened and be assured that it will not happen again. At this juncture, apologies which are ‘statements acknowledging error and its consequences, including accepting responsibilities and communication of regrets’ can reduce the anger as well as patient desire to retaliate. Nevertheless, apologies may also have the potential to be seen as admissions of guilt by the medical practitioner, thus, exposing him to risks of impending lawsuits. In weighing the drawbacks of apologies against their benefits, several countries have enacted ‘apology laws’ that mandate open disclosure of medical errors but shield those who apologise from legal liability. This paper seeks to discuss the role of apologies in the resolution of medical disputes and the barriers faced by medical practitioners in subjecting themselves to acts of open disclosure after a mishap. Nevertheless, the inculcation of a sustainable culture of honesty, openness and respect is fundamental to improve patient safety and public trust in the healthcare system.